Investigating readiness of the arrival of industrial revolution 4.0 among students in higher learning institution / Nurul Munirah Azamri and Nadiah Zubbir - Azamri, Nurul Munirah; Zubbir, Nadiah (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
This study is intended to identify whether the students of higher learning institutions are ready of the arrival of the current worldwide emergence of Internet of Things (IOT) which then leads to the Industrial Revolution 4.0 (IR 4.0). The updated advancement has been identified to bring positive results towards integration of this emergence and the students’ learning. This is in turn suggests for the concept of IR .0 to be implemented onto them. In order to deal with the challenge brought by IR 4.0, Professor Klaus Schwab, Founder and Executive Chairman of the World Economic Forum has enlightened that university students must enhance their 4C elements which are Critical Thinking and Problem Solving, Communication, Collaboration and Creativity. A total of 50 students from different courses of Diploma el participated in this study. A set of questionnaires was distributed to collect relevant findings. This study reveals that the students are ready for the arrival of IR 4.0 as they are encouraged with various learning styles, interest, motivation and student’s engagement in the new norm of the industrial motivation. The outcomes from this study will assist students and also instructors through the implementation of IR 4.0 in teaching and learning process in the classroom.